Consumer’s Perception towards Quick Response (QR) Payment in Kathmandu Valley - Adhikari, Kranti (Nepalese Journal of Management, 2024)
This study examines the consumer’s perception towards Quick Response (QR) payment in Kathmandu Valley. Behavioral intentions to use QR is selected as dependent variable. The selected independent variables are perceived ease of use, perceived usefulness, perceived security, perceived trust, self-efficacy and service quality. The study is based on primary data of 196 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression model are estimated to test the significance and importance of different factors that affect user’s perception towards Quick Response (QR) payment in Kathmandu Valley. The study showed that perceived ease of use has a positive effect on behavioral intention to use QR. It indicates that more user-friendly QR technology leads to increase in the level of user acceptance to use QR. Similarly, perceived usefulness has a positive effect on behavioral intention to use QR. It indicates that greater benefits of utilizing the QR code technology leads to increase in the level of user acceptance to use QR. Likewise, perceived security has a positive effect on behavioral intention to use QR. It indicates that safer the technology for QR payment technology, higher would be the level of user acceptance to use QR payment technology. Further, perceived trust has a positive effect on behavioral intention to use QR payment technology. It indicates that higher the reliability of QR payment, higher would be the level of user acceptance to use QR payment technology. In addition, self efficacy has a positive effect on behavioral intention to use QR. It indicates that higher the beliefs of users’ towards QR payment, higher would be the level of user acceptance to use QR payment technology. Moreover, service quality has a positive effect on behavioral intention. It indicates that better service quality of QR payment technology leads to increase in the level of user acceptance to use QR payment technology.